Pandang Dunia: Penentu Kekuatan dan Perubahan Tradisi Masyarakat Tradisional - Kamuri, Johanis Putaratama (UI Scholars Hub, 2021)
Traditional society is a society that is strongly influenced by tradition. However, the fact is a society can also change such strong tradition. This research aims to understand the driving force that allows the influence of tradition and changes in traditions by traditional societies. Through a systematic review of relevant literature, this research complements Giddens' structuration theory with MacIntyre's thoughts about cultural components that make up the cognitive structure and shows that worldview - a virtual structure in cognition that corresponds to the structure of society - is the force that determines the influence and change of traditions. Therefore, different from studies that point to external forces such as education, globalization, and modernization as causes of changes in traditional societies, this study refers to worldview as an agent's internal capacity. The influence of tradition on agents and changes in tradition caused by various external forces is mediated by worldview; thus, the power of tradition presupposes the power of worldview, and changes in tradition presuppose a change in worldview.